MENTAL TOUGHNESS AND PSYCHO-SOCIAL REACTIONS IN COVID-19 SUFFERERS: A MEDIATING ROLE OF EMBITTERMENT - Haroon, Linta; Zahra, Sayyeda Taskeen (Journal of Postgraduate Medical Institute, 2024)
Objective: The objective of this paper was to explore the mediating role of embitterment in the association of mental toughness and psychosocial reactions in COVID-19 sufferers. Methodology: The cross-sectional study was conducted at three government and private universities of Islamabad Pakistan chosen through random selection and comprised a purposive sample of 202 young adults of BS degree, between ages limit 18-25. The overall mean age was 20.4 years with a standard deviation of 1.47. Boys constituted 49% and girls constituted 51% of the total sample. Study sample included 17% participants that had been infected with COVID-19, 52% whose family member had been infected and 15% had experienced the death of a family member due to COVID-19, 12% fell into 2 of the categories while 4% experienced all three circumstances. Results: Results show that male participants scored higher on psycho-social reactions as compared to females. Findings revealed a significant positive relationship of embitterment with psychosocial reactions (B=.49, SE=.06, p < .001). Embitterment also has a negative relationship with mental toughness (B = - .42, SE= .06, p <.001) Conclusion: COVID-19 sufferers faced psychological challenges along with health issues which led to extreme psychosocial reactions and feelings of embitterment, whereas mental toughness functioned as a protective factor.